Perceived Benefits and Barriers of a COVID-19 Test to Stay Program in a School District Serving Black or African American People With Low Income, December 2021. (May 2023) - Kamitani, Emiko; Holman, Emily J.; Philpott, David; Parasram, Vidisha D.; Ruth, Laird J.; Onyeuku, Chisom; Carter, Brittani; Gwynn, Eugenia; Beck, Timothy W.; Regan, Kelly; Hagler, LaVerne R.; Clark, Angela; et al.
Objectives: Quarantine after exposure to COVID-19 has resulted in substantial loss of in-person learning in schools from prekindergarten through grade 12. Test to Stay (TTS), a strategy that limits the spread of SARS-CoV-2 while prioritizing in-person learning, requires substantial investment in resources. The objective of this study was to assess the perceived benefits, barriers, and facilitators of implementing TTS in an urban school district in the Midwest serving primarily Black or African American people with low income. Methods: In December 2021, we used a concurrent mixed-methods approach to understand perceived benefits, barriers, and facilitators of implementing TTS by combining quantitative analysis of telephone surveys conducted with parents (n = 124) and a qualitative inquiry involving key informants from the school district and local health department (n = 22). We analyzed quantitative data using descriptive statistics. We used thematic analysis to analyze qualitative data. Results: Quantitative findings showed that parents supported TTS because it was convenient (n = 83, 97%) and effective (n = 82, 95%) in keeping students learning in person (n = 82, 95%) and preventing the spread of COVID-19 (n = 80, 93%). Qualitative interviews with informants found that having a clear protocol and assigning staff to specified tasks allowed for successful TTS implementation. However, insufficient staffing and testing resources, parent mistrust of testing, and lack of communication from schools were perceived barriers. Conclusion: The school community strongly supported TTS despite the many implementation challenges faced. This study emphasized the importance of ensuring resources for equitable implementation of COVID-19 prevention strategies and the critical role of communication.